Rice Lines (Oriza sativa L.) Selection on Some Agronomic Characters - Miranda Ferwita Sari; Jaenudin Kartahadimaja; Destieka Ahyuni; Lina Budiarti (Faculty of Agriculture, Pattimura University, 2021)
Most of the Indonesian population uses rice as main source of carbohydrates. The need for rice increases every year, but rice production and rice harvest area decreases every year. One way to overcome this problem is using new variety that has high productivity. This research aims to determine the agronomic characters that can be used as character selection and to select the best lines based on the character selection. The research was conducted at the Seed Teaching Farm Field of Seed Technology Study Program, Politeknik Negeri Lampung in August - December 2020. The treatment design was arranged in randomized complete block design with 1 factor (line), 3 blocks, and 3 replications. The treatments tested were 6 lines of rice plants assembled by Politeknik Negeri Lampung, namely B1, B2, B3, B4, K, L2 lines with 2 comparison varieties Ciherang and Gilirang. The characters observed were plant height, total number of tillers, number of productive tillers, flowering age and harvest age. The data from the observations were processed with SAS software and the analysis of real variance was continued by using Duncan's Multiple Range Test (DMRT) with an error rate of 5%. The results of this research indicate that the characters of the total number of tillers and the number of productive tillers can be used as a selection character and the lines that have superior characters are the K and L2 lines.Keywords: Rice Lines, Agronomic Character, Selection